The Effect of Immediate and Lifetime Experience of Reading Horizontal and Vertical Texts on Chinese Speakers’ Temporal Orientation - Chen, Jenn-Yeu (Journal of cognition and culture, 2015)
The present study examined participants’ performance on a temporal judgment task while holding language constant but varying their lifetime and immediate reading experience of horizontal and vertical texts. Chinese participants from Taiwan and China were randomly assigned to a reading task involving horizontally or vertically arranged texts. A temporal judgment task (spatial-temporal association of response codes or starc) followed the reading task, asking the participants to judge if the event depicted in a second picture occurred earlier or later than that in a first picture. Responses were faster when the left keys represented the ‘earlier’ responses than when the right keys did (a starc effect). Half of the participants responded with horizontally oriented keys while the rest with vertically oriented keys. For the Taiwan participants, the overall starc effect was greater when the response keys were vertical than horizontal, but no difference was observed for the China participants. A questionnaire indicates that the two groups of participants had similar lifetime experiences of reading horizontal texts, but the Taiwan participants read vertical texts in their life far more frequently than the China participants. Immediate reading experiences interacted with lifetime experiences in modulating the vertical bias. For the Taiwan participants, the vertical bias was strong following the vertical prime, but disappeared following the horizontal prime. For the China participants, the horizontal prime led to no vertical bias whereas the vertical prime brought about a horizontal bias. We conclude that the directionality of orthography and speakers’ immediate and lifetime reading experiences can better explain the vertical bias (or the lack of it) in the Chinese speakers’ temporal thinking. The findings, however, may be interpreted as constituting a different manifestation of linguistic relativity and recast under a broader framework of the extended-mind hypothesis of human cognition.